PERLINDUNGAN HUKUM TERHADAP HAK-HAK TERDAKWA DALAM PENYELESAIAN PERKARA PIDANA DI GORONTALO - Nopiana Mozin (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Based on research results witness or victim protection is regulated in Law no. 13 of 2006 and to find out how the legal protection of the rights of the defendant in criminal cases in Gorontalo the violation of the defendant was carried out by the investigator both from the beginning of the process until the end of the process. The human rights law must be fulfilled and there are several violations committed by the investigator both intentionally or unintentionally. The defendant's human rights are listed in Law No. 8 of 1981 concerning criminal procedural law in article 98 paragraph 1 explains"If an act which forms the basis of an indictment in an examination of a criminal case by a district court results in a loss for another person, the presiding judge may at the request of that person determine to incorporate the case for the compensation claim to the criminal case".Paragraph (2) explains;"The request referred to in paragraph (1) may only be submitted at the latest before the public prosecutor recommends a criminal charge. In the event that the public prosecutor is not present, the request is submitted no later than before the judge passes the sentence ".The defendant's human rights law is a right that must be carried out by the investigator from the beginning of the process until the end of the investigation process.